1998
DOI: 10.1046/j.1523-5378.1998.08010.x
|View full text |Cite
|
Sign up to set email alerts
|

RFLP and RAPD Analysis of In Vivo Genetic Interactions Between Strains of Helicobacter pylori

Abstract: These findings support the development of genetic heterogeneity of H. pylori during long-term colonization either by genetic drift or by in vivo recombination. Such genomic modification in vivo could explain the naturally occurring heterogeneity of H. pylori.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 17 publications
1
10
0
Order By: Relevance
“…Once established, a strain could interfere with the establishment of a subsequent strain even when the latter was more fit to colonize mice. This phenomenon was previously described by Danon et al, who showed that the implantation of a first strain in the mouse could prevent the implantation of a mixture of other strains (7). This finding could be the consequence of the immune response against the first strain (IS) being strong enough to inhibit the implantation of the second strain.…”
Section: Discussionsupporting
confidence: 57%
“…Once established, a strain could interfere with the establishment of a subsequent strain even when the latter was more fit to colonize mice. This phenomenon was previously described by Danon et al, who showed that the implantation of a first strain in the mouse could prevent the implantation of a mixture of other strains (7). This finding could be the consequence of the immune response against the first strain (IS) being strong enough to inhibit the implantation of the second strain.…”
Section: Discussionsupporting
confidence: 57%
“…They found that only one bacterial strain emerged, and it was usually the primary strain. These results are supported by Danon et al, where some evidence is provided that an established H. pylori strain can prevent colonization by a challenging strain (14). In contrast, with two different mouse-adapted strains of H. pylori that colonize distinct stomach regions, Akada et al showed that both strains can simultaneously infect, and superinfection does not alter colonization of either strain (1).…”
Section: Discussionmentioning
confidence: 78%
“…Using the silver-stained slides from the 6-and 15-month time points, five areas of the stomach (antrum, antrum-body transitional zone, body, body-cardium transitional zone, and cardium regions) were assessed for the level and presence of bacteria using a grading system from 0 to 4 as described previously (9,36). Briefly, a grade of 0 indicates no bacteria observed, while a grade of 4 indicates heavy colonization where all crypts were densely packed.…”
Section: Mouse Infections (I) Isolation Of New Mouse-colonizing Stramentioning
confidence: 99%
“…The mouse-adapted SS2000 strain colonized to a level approximately 0.5 log unit higher than the pre-mouse-adapted strain (PMSS2000) in C57BL/6 mice; thus, some host adaptation appears to have occurred during the isolation of this strain. Host adaptation of H. pylori has been reported to occur in mice (9,31,39), gerbils (23), primates (11), piglets (15), and humans (18,24,25). The mechanisms of these adaptations are largely unknown, although they are likely to involve genomic variations (3,18).…”
Section: Vol 72 2004 Chronic H Pylori Infection In the Mouse Modelmentioning
confidence: 99%